In vitro drug release of ibuprofen loaded PLGA microparticles / Kamalunisa Mohd Alwai - Mohd Alwai, Kamalunisa (2007)
The purpose of using PLGA polymer in this experiment is to prolong the action of ibuprofen. Thus the number of administration can be reduced and this may increase patient compliance due to decrease number of pills or capsules to be taken per day. This study is designed to investigate the rate of ibuprofen release from the drug, the mechanism associated with the drug release from the PLGA, the effect of pH and temperature to ibuprofen release from the microparticles and how different ratio of polymer to the drug can affect the morphology of the microparticles. Concentration of ibuprofen release from the polymer was measured by using UV-Vis spectrophotometer and the surface morphology was determined by using scanning electron microscope (SEM). In vitro release shows that, at physiological temperature, ibuprofen released at faster rate compared at 25° C . At higher pH, about 100% of drug being released while at gastric pH 90% of drug are being released. Different ratio of polymer to the drug concentration does not affect the surface morphology of the microparticles.